Characterization and antibacterial activity of edible films based on carboxymethyl cellulose, Dioscorea opposita mucilage, glycerol and ZnO nanoparticles. (1st July 2021) - Li, Xiaojing; Ren, Zeyue; Wang, Ruijiao; Liu, Lu; Zhang, Jie; Ma, Fanyi; Khan, Md. Zaved Hossain; Zhao, Dongbao; Liu, Xiuhua
Highlights: The films based on CMC, DOM, glycerol and ZnO-NPs were prepared and characerised. CMC-to-DOM ratio of 1:1 exhibits smooth surface. The films with 2.0 g ZnO-NPs presented higher antibacterial activity. The prepared films with ZnO-NPs have a great potential to apply in food packaging. Abstract: The edible films composed of carboxymethyl cellulose (CMC), glycerol, mucilage from Chinese yam (DOM) and ZnO nanoparticles (ZnO-NPs), were prepared by a casting method. To evaluate the applicability for food packaging, prepared films were characterised morphological, physical, rheological, mechanical and barrier properties, performed FT-IR, thermal analysis, and finally investigated the antibacterial activity and acute oral toxicity of films. The surface of films presented irregular arrangement with nanoparticles combined in the networks, suggesting the best "CMC to DOM weight ratio" of approximately 1:1 could provide a smooth surface. The films with 2.0 g ZnO-NPs presented antibacterial effects against both Gram-positive ( S. aureus) and Gram-negative ( E. coli ) bacteria. With the increase of DOM, the antibacterial rate dropped at 400 and 450 μL/mL. The film-forming solutions with higher ZnO-NPs content display shear-thinning properties and liquid-like behaviour. The edible films have a great potential to be used in application in food packaging.